The spectral signature analysis of inland and coastal water bodies acquired from field spectroradiometric measurements - Papoutsa, Christiana; Akylas, Evangelos; Hadjimitsis, Diofantos G. (My University, 2013)
The main goal of this research is to examine the optical properties of different water bodies such as coastal water; oligotrophic and eutrophic inland water by observing their spectral signatures. Spectral profiles of sampling points, which correspond to water bodies with different water quality characteristics, are extracted and analyzed. Field spectroscopy is a very important tool giving critical information for the comprehension of spectral signatures of different water bodies. Field spectroradiometric measurements can assist to improve or develop new algorithms and methodology enables to classify several water bodies according to their water quality characteristics using remotely sensed data. Field spectroradiometric data presented at this study were obtained for inland water in Asprokremmos Dam, Paphos District/Cyprus; in Larnaca’s Salt Lake, Larnaca District/Cyprus; and in Karla Lake, Volos District/Greece and for coastal water in Zugi-Vasilikos-Old Harbour, Limassol District/Cyprus. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: Physical oceanography; Water; Algorithms; Field spectroscopy; Optical properties